Systematic analysis of early phase clinical studies for patients with breast cancer: Inclusion of patients with brain metastasis. (April 2017) - Costa, R.; Gill, N.; Rademaker, A.W.; Carneiro, B.A.; Chae, Y.K.; Kumthekar, P.; Gradishar, W.J.; Kurzrock, R.; Giles, F.J.
Highlights: Brain metastasis is a growing complication of metastatic breast cancer. Better treatment is needed for patients with breast cancer brain metastasis. Few drug trials clearly allow for enrollment of patients with brain metastasis. Abstract: Purpose: This systematic review aims to better define the limitations and patterns with which patients with MBC and CNS metastasis are enrolled into early phase developmental therapeutics trials. Methods: In June 2016, PubMed search was conducted using the following keywords: "Breast cancer". Drug-development phase 1, phase 2 or phase 1/2 trials for patients with MBC were included. Multiple-histology trials and trials without an efficacy endpoint were excluded. Results: In total, 1474 studies were included; Inclusion criteria for 423 (29%) allowed for CNS metastasis, 770 (52%) either excluded or did not document eligibility of patients with CNS disease. Trials accruing patients with HER2-positive MBC and including targeted therapies had higher odds of allowing for patients with CNS disease (adjusted OR 1.56, 95% CI 1.08–2.2.6; p = 0.019 and 1.49, 95% 1.08–2.06; p = 0.014, respectively). There were also higher odds of accrual of patients with CNS involvement into clinical trials over time (odds ratio = 1.10, 95% CI 1.07–1.12; p < 0.0001). Conclusion: Most published early phase clinical trials either did not clearly document or did not allow for accrual of patients with CNS disease. Early phase trials with targeted agents or enrolling HER2+ MBC had higher odds of permitting CNS metastases.